2001
DOI: 10.1200/jco.2001.19.17.3750
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Outcomes After Primary Androgen Deprivation Therapy: Results From the Prostate Cancer Outcomes Study

Abstract: Most endocrine-related health outcomes are similar after surgical versus medical primary hormonal therapy. Stage at diagnosis had little effect on outcomes. These results provide representative information comparing surgical and medical AD therapy that may be used by physicians and patients to inform treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(138 citation statements)
references
References 20 publications
2
128
0
8
Order By: Relevance
“…A common practice outside clinical trials is to apply AD for 3 -6 months, but treatments as long as several years are also practised. The use of AD appears to be most common in early-stage disease (T1 -T2), as reported by Potosky et al (2001), these being patients who are usually long-term survivors in PC. At least 22 000 PC men each year in the US have been estimated to receive hormonal therapy (Potosky et al 2001).…”
mentioning
confidence: 92%
“…A common practice outside clinical trials is to apply AD for 3 -6 months, but treatments as long as several years are also practised. The use of AD appears to be most common in early-stage disease (T1 -T2), as reported by Potosky et al (2001), these being patients who are usually long-term survivors in PC. At least 22 000 PC men each year in the US have been estimated to receive hormonal therapy (Potosky et al 2001).…”
mentioning
confidence: 92%
“…Potosky et al 49 in a prospective cohort of 431 men, showed that the percentage of men who were sexually inactive increased from 48% to 83% after orchiectomy and from 45% to 80% after gonadotropinreleasing hormone agonist administration. Marumo et al 50 observed in nine sexually active prostate cancer patients who underwent ADT with 3.75 mg of leuprorelin acetate every 4 weeks as monotherapy, that a reduction in serum testosterone concentrations to levels inferior to 10 ng dl 21 at 12 weeks, preceded total suppression of sexual activity (no intercourse for 12 weeks during treatment) in all patients.…”
Section: Sexual Activitymentioning
confidence: 99%
“…Besides hot flushes and sexual dysfunction, a higher incidence of breast swelling with LHRH analogues compared to orchiectomy has also been reported (24.9 % vs. 9.7 %) [7]. In addition, contrary to popular belief, LHRH agonist therapy significantly decreases the testicular weight.…”
Section: Discussionmentioning
confidence: 99%